The Influence of Service Quality and Work Discipline on Patient Satisfaction at the Tambah Subur Community Health Center UPTD, Way Bungur District, East Lampung - Friska Silvia Vitarina (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the influence of service quality and work discipline on patient satisfaction at UPTD Tambah Subur Health Center. The background of this research is based on the importance of highquality health services and the discipline of healthcare workers in providing optimal services to the community. Patient satisfaction is an important indicator in assessing the success of a health service institution, as it directly reflects the quality of service provided. This research uses a quantitative approach with statistical analysis methods. Data was collected through the distribution of questionnaires to patients who had received services at the Tambah Subur Health Center. The sample was selected using purposive sampling techniques based on predetermined criteria. The independent variables in this study are service quality (X1) and work discipline (X2), while the dependent variable is patient satisfaction (Y). Data were analyzed using multiple linear regression methods to determine the extent of the influence of each independent variable on the dependent variable. The results of the study show that both service quality and work discipline have a positive and significant effect on patient satisfaction, both partially and simultaneously. These findings indicate that improving service quality and employee discipline can be an important strategy in efforts to increase patient satisfaction and public trust in the services provided by Tambah Subur Health Center.